Obestatin and Nerve Growth Factor in Patients with Metabolic Syndrome - Kheirouri, Sorayya; Jabbari, Masoumeh; Alizadeh, Mohammad (Progress in Nutrition, 2018)
Purpose: Obestatin and nerve growth factor (NGF) have recently been introduced as adipokines. Several evidences have implicated involvement of these two peptides in some metabolic disorders. We aimed to investigate the association between serum obestatin and NGF levels with metabolic syndrome (MetS) parameters in women. Methods: Forty three female patients with MetS and 43 BMI-matched healthy women as control group, aged 30- 50 years, participated in the study. Anthropometric parameters, blood pressure, fasting serum obestatin, NGF, TG, TC, HDL-C, LDL-C,FBS, insulin and HOMA-IR were measured. The relationship between serum levels of obestatin and NGF with measured variables was analyzed. Results: Women in MetS group had significantly higher values of WHR (p = 0.01), systolic (p = 0.01) and diastolic blood pressure (p = 0.01), TG (p < 0.001), FBS (p < 0.001), insulin (p = 0.004), HOMA-IR (p < 0.001) and lower level of HDL-C (p < 0.001) as compared with healthy women. Serum levels of obestatin partially (p = 0.08) and NGF levels significantly was lower (p = 0.02) in MetS group than control. Both serum levels of NGF (β = -0.41, p = 0.01) and obestatin (β = -0.38, p = 0.02) were negatively associated with serum TG levels in MetS group. There was significant and positive association between serum obestatin and NGF levels in MetS group (β =0.41, p= 0.01). Conclusion: The results indicating that obestatin and NGF might be important regulators of TG level and through this involved in the pathogenesis of MetS.